Antibacterial Activity of Honey Pineapple Peel Extract (Ananas comosus [L] Merr.) against MethicillinResistant Staphylococcus aureus - Imraatul Husniah; Tri Umiana Soleha (Warmadewa University, 2023)
Methicillin-resistant Staphylococcus aureus (MRSA) infection is a global health problem that needs to be answered by developing a synthetic or natural antibacterial to overcome the problem. The honey pineapple peel contains potentially antibacterial compounds such as bromelain and flavonoid. This study aims to determine the antibacterial activity of honey pineapple peel extract (Ananas comosus [L] Merr.) against MRSA. The design of this study was a true experimental study with a post-test control group design. This study examined the antibacterial activity of honey pineapple peel extract at concentrations of 100%, 50%, 25%, 12.5%, 6.25%, 3.125%, and 1.56% against MRSA bacteria by measuring minimum inhibitory concentration (MIC) with dilution method and minimum bactericidal concentration (MBC). The results of this study show that MIC was obtained at concentrations of 50 % and MBC at extract with a concentration of 100 %. There is an antibacterial activity of honey pineapple peel extract (Ananas comosus [L] Merr.) against MRSA. Keywords: Antibacterial Activity, Honey Pineapple Peel, MRSA